Teachers’ Strategies in Implementing Differentiated Instruction on Plane Figures: A Qualitative Case Study Using NVivo - Sabitillah, Lisa; Lubis, Wildansyah; Maisura, Maisura (SAINTIS Publishing, 2025)
Differentiated instruction is considered a key approach to accommodate the diverse characteristics of students in mathematics learning, particularly in plane figures material at the elementary school level. However, its implementation in the field still faces challenges, and in-depth exploration of teacher strategies through a qualitative approach remains limited. This qualitative case study aims to explore teacher strategies in implementing differentiated instruction on plane figures material in fourth grade at UPTD SD Negeri 4 Bireuen. Data were collected through in-depth interviews with three teachers, classroom observation, and documentation studies, analyzed thematically with the assistance of NVivo 15 software to ensure systematic and in-depth analysis. The results reveal that teacher strategies are integrated into four main pillars: (1) content differentiation through adaptation of presentation modes (visual, auditory, kinesthetic) and learning contracts; (2) process differentiation based on heterogeneous grouping and contextual prompting questions; (3) product differentiation by providing choice in task forms and clear assessment rubrics; and (4) management of a collaborative learning environment. These strategies are supported by the application of the Problem Based Learning (PBL) model and interactive digital media (game-based learning). The study concludes that the success of differentiated instruction depends on the multidimensional synergy among learning elements and the teacher's commitment to being a reflective practitioner responsive to each individual student's needs. These findings provide a contextual strategic framework for teachers in implementing the student-centered Merdeka Curriculum.